Occurrence of dysentery‐like diarrhoea associated with Brachyspira suanatina infection on a German fattening pig farm. (17th February 2018) - Rohde, Judith; Majzoub‐Altweck, Monir; Falkenau, Almuth; Hermanns, Walter; Burrough, Eric R; Ritzmann, Mathias; Stadler, Julia
Abstract : The anaerobic intestinal spirochaete Brachyspira (B. ) suanatina was first described in 2007 but since then no further isolates have been reported from pigs. Accordingly, when the species was validly published in 2016, the overall occurrence and clinical relevance in pigs were unknown. In a fattening farm in southern Germany, mucohaemorrhagic diarrhoea was observed in 60 per cent (750 animals) of the finisher pigs. A diagnostic workup including Brachyspira culture, Salmonella culture, Lawsonia intracellularis‐ specific, B. hyodysenteriae ‐specific and B. pilosicoli ‐specific multiplex PCR and postmortem examination of severely affected pigs was performed. Tests for Salmonella species, Lawsonia intracellularis and B. hyodysenteriae were all negative. Gross and microscopic lesions were in agreement with dysentery and spirochaetes could be demonstrated by silver staining in tissue samples of the caecum at the ileal papilla. B. suanatina was cultured from faeces or colon of all (five) animals sampled and identified using nox ‐RFLP, partial nox ‐gene‐sequencing and matrix‐assisted laser desorption ionization‐time of flight mass spectrometry (MALDI‐TOF MS). According to the initial report from Scandinavia, B. suanatina can be isolated from birds and cross‐species infection could be demonstrated infecting pigs with an avian isolate. Thus outdoor production as in the case presented here and international trade may pose a risk for infection of naive herds.